When death thoughts knock, mindfulness protects life meaning from existential threat - Del Rosario, Francis Edward N. (Animo Repository, 2019)
Terror Management Theory (TMT) posits that unconscious death thoughts undermine meaning in life under certain dispositional constraints. One disposition that has been established to be an effective buffer against the harmful effects of mortality salience is mindfulness. This study aimed to determine whether trait mindfulness would moderate death thought accessibility (DTA) and meaning in life, such that those who report low mindfulness and high DTA would reflect lower meaning in life scores. Participants aged 18 to 25 (N=139) responded to an online survey, completing self-report trait measures of mindfulness (MAAS), meaning in life (MLQ-P), and unconscious death thoughts as measured by a word-fragment test. Results show that for less mindful individuals, those with high DTA report lower levels of meaning in life; while for mindful participants, meaning in life is relatively the same regardless of DTA. While the results are consistent with theory and research, mindfulness does not significantly moderate the link between DTA and meaning in life. Implications of these findings on existential concerns of adolescents are discussed.